2021
DOI: 10.1007/s13304-021-01054-y
|View full text |Cite
|
Sign up to set email alerts
|

Side-to-side esophagogastric anastomosis for minimally invasive Ivor-Lewis esophagectomy: operative technique and short-term outcomes

Abstract: Totally minimally invasive Ivor-Lewis esophagectomy (TMIIL) is associated to lower rate of post-operative complication, decreases length of hospital stay and improves quality of life compared to open approach. Nevertheless, adaptation of TMIIL still proceeds at slow pace, mainly due to the difficulty to perform the intra-thoracic anastomosis and heterogeneity of surgical techniques. We present our experience with TMIIL utilizing a stapled side-to-side anastomosis. We retrospectively evaluated 36 patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Slankamenac et al first developed Comprehensive Complications Index (CCI) in 2013 to integrate complications with their respective severity ( 11 ). CCI is a more sensitive complication index than the Clavien–Dindo (CD) classification and has been confirmed as a promising score system to evaluate the severity of complications after esophagectomy ( 12 , 13 ). The CCI values range from 0 to 100; a value of 0 reflects the absence of complications, while a CCI of 100 indicates that the patient has died due to complications.…”
Section: Methodsmentioning
confidence: 99%
“…Slankamenac et al first developed Comprehensive Complications Index (CCI) in 2013 to integrate complications with their respective severity ( 11 ). CCI is a more sensitive complication index than the Clavien–Dindo (CD) classification and has been confirmed as a promising score system to evaluate the severity of complications after esophagectomy ( 12 , 13 ). The CCI values range from 0 to 100; a value of 0 reflects the absence of complications, while a CCI of 100 indicates that the patient has died due to complications.…”
Section: Methodsmentioning
confidence: 99%
“…Minimally invasive surgery is now common in clinical practice not only in general surgery but also in oncological pathologies [28,[194][195][196][197][198][199][200][201][202][203].…”
Section: Post-operative Pancreatic Fistulamentioning
confidence: 99%
“…However, as the authors mentioned, a relatively high anastomotic stricture rate was observed. A study describing intrathoracic anastomoses using circular staplers showed similar stricture rates [ 3 ], whereas other studies showed relatively low anastomotic stricture rates [ 4 , 6 ]. Therefore, it may be necessary to consider other factors that may affect stricture rates, in addition to the fact that pulling the gastric tube may lead to stenosis.…”
mentioning
confidence: 99%